Resolving Shelf Break Exchange Around the European Northwest Shelf. Issue 22 (20th November 2018) - Graham, Jennifer A.; Rosser, Jonathan P.; O'Dea, Enda; Hewitt, Helene T.
Abstract: Shelf seas act as a significant sink of carbon within the global ocean. This occurs as carbon is exported beneath the permanent oceanic thermocline through the downwelling circulation across the shelf break. This downwelling circulation is quantified here using two regional ocean model configurations of the European northwest shelf, with differing resolution (7‐ and 1.5‐km grid spacing). The dominant mechanisms and impact of model resolution are assessed along the length of the shelf break. The total downwelling circulation is stronger at higher resolution, due to an increased on‐shelf transport at internal depths (20–150 m) and increased off‐shelf transport at the base of the water column. At internal depths, these differences increase seasonally, influenced by stratification. Key processes in cross‐shelf exchange only begin to be resolved at O(1 km), implying that global models currently used to assess the carbon cycles will be missing these processes. Plain Language Summary: Shallow seas over continental shelves have a large impact on the global environment, acting as a sink in the global carbon cycle. Despite their importance, shelf seas are not well represented in global climate simulations. Climate models struggle to reproduce exchange between the shelf seas and deep ocean, due to the combination of large and small‐scale processes involved. Around the European northwest shelf, water typically flows onto the continental shelf (toward the coast) in the surface ocean and off‐shelf (toward the deep ocean) at the bottom. This downwelling circulation allows carbon to be exported into the deep ocean, away from the atmosphere. The strength of the downwelling circulation is calculated here using two ocean models with different horizontal resolution (7‐ and 1.5‐km grid spacings). These models represent different processes, dependent on their resolution. The higher‐resolution model (1.5‐km grid spacing) is found to have a stronger downwelling circulation, and these differences increase seasonally during the summer. This shows that small‐scale processes, which are missing in lower resolution models, have a large impact on exchange between the shelf seas and deep ocean. These processes are missing in many global models used for long‐term climate projections. Key Points: Horizontal resolution strongly impacts exchange between shelf seas and the deep ocean Internal processes have a significant impact, as on‐shelf transport increases within 20‐ to 150‐m depth Increased off‐shelf flux below 150‐m depth has potential impacts for the shelf sea carbon pump